Análise estereológica do córtex cerebral e do hipocampo de camundongos sob o uso de esteroides anabalizantes - Silva, Dauanda Kécia (2014)
Anabolic androgenic steroids (AAS) are testosterone synthetic derivatives. In recent decades, the importance given to body image has grown dramatically, as well as the consumption of so-called "body image drugs", which include ASS. The aim of this study was to analyze the effects of AAS chronic use in the amount of limbic, motor, sensory and Ca1, Ca2, Ca3 hippocampal areas nerve cells of mice. Were used, 32 male mice divided into 4 groups (n=8): G1: control, G2: treated with anabolic steroid Durateston® (testosterone propionate, testosterone fempropionate, testosterone isocaprionate, testosterone decanoate), G3: treated with steroid anabolic Deca Durabolin® (nandrolone decanoate) and G4: treated with both steroids concomitantly. The mice were treated for two (2) months, receiving 83.3 mg / kg / week of Durateston® and 16.6 mg / kg / week of Deca Durabolin and swimming three times a week. After euthanasia their brains were removed, washed and stored in 4% formaldehyde. The fragments were processed according to standard histological procedures in conventional sequence; cresyl violet staining and subsequent analysis using to simple random count methodology. The results show a significant reduction in number of neuron bodies in limbic, motor and sensory areas of cerebral cortex and the hippocampus Ca1 and Ca2 areas. The results suggest that chronic use of AAS can be harmful to nervous system, since the reduction of neuron bodies can bring structural and functional damage to the brain.